Genome Assembly for a Yunnan-Guizhou Plateau “3E” Fish, Anabarilius grahami (Regan), and Its Evolutionary and Genetic Applications - Jiang, Wansheng; Qiu, Ying; Pan, Xiaofu; Zhang, Yuanwei; Wang, Xiaoai; Lv, Yunyun; Bian, Chao; Li, Jia; You, Xinxin; Chen, Jieming; Yang, Kunfeng; Yang, Jinlong; et al. (Frontiers in Genetics, 2018)
A Yunnan-Guizhou Plateau fish, the Kanglang white minnow (Anabarilius grahami), is a typical “3E” (Endangered, Endemic, and Economic) species in China. Its distribution is limited to Fuxian Lake, the nation’s second deepest lake, with a significant local economic value but a drastically declining wild population. This species has been evaluated as VU (Vulnerable) in the China Species Red List. As one of the “Four Famous Fish” in Yunnan province, the artificial breeding has been achieved since 2003. It has not only re-established its wild natural populations by reintroduction of the artificial breeding stocks, but also brought a wide and popular utilization of this species to the local fish farms. Anabarilius grahami has become one of the main native aquaculture species in Yunnan province, and the artificial production has been emerging in steady growth each year. To promote the conservation and sustainable utilization of this fish, we initiated its whole genome sequencing project using an Illumina Hiseq2500 platform. The assembled genome size of A. grahami is 1.006 Gb, accounting for 98.63% of the estimated genome size (1.020 Gb), with contig N50 and scaffold N50 values of 26.4 kb and 4.41 Mb, respectively. Approximately about 50.38% of the genome was repetitive. A total of 25,520 protein-coding genes were subsequently predicted. A phylogenetic tree based on 4,580 single-copy genes from A. grahami and 18 other cyprinids revealed three well-supported subclades within the Cyprinidae. This is the first inter-subfamily relationship of cyprinids at genome level, providing a simple yet useful framework for understanding the traditional but popular subfamily classification systems. Interestingly, a further population demography of A. grahami uncovered a historical relationship between this fish and Fuxian Lake, suggesting that range expansion or shrinkage of the habitat has had a remarkable impact on the population size of endemic plateau fishes. Additionally, a total of 33,836 simple sequence repeats (SSR) markers were identified, and 11 loci were evaluated for a preliminary genetic diversity analysis in this study, thus providing another useful genetic resource for studying this “3E” species.